Chiefs and Rural Health Services in South-Western Nigeria, c. 1920—c. 1950s - Adetiba, Adedamola; Msindo, Enocent (Social history of medicine : the journal of the Society for the Social History of Medicine, 2022)
Summary This article examines the role of African chiefs in the administration of colonial medicine in rural south-western Nigeria, emphasising the adaptive ways they navigated a difficult position between colonial medical authorities and indigenous medical legitimacy. Whereas colonial authorities expected chiefs to enforce medical policies and to encourage their subjects to use medical facilities, Africans wanted chiefs to defend and promote Yoruba medical and religious practices that colonial authorities and missionaries usually undermined. By supporting established African healing systems, chiefs stood to gain political mileage and favour with traditional healers. Furthermore, we argue that although African chiefs cooperated with the government in implementing health policies, they had a difficult relationship with sanitary inspectors who enforced sanitary regulations in ways that bred resentment. In the 1940s, Yoruba chiefs advocated for more rural health services, perhaps to pacify the rising nationalist movement that would have made them irrelevant had they not cooperated.